FEVER OF UNKNOWN ORIGIN: DESCRIPTIVE STUDY - Yu. A. Perova; N. Ramos Vicente; L. Alandete German; J. Izquierdo Alabau; G. Fernando Lascurain; J. Martinez Mendieta; D. M. Sanchez Escobedo (Архивъ внутренней медицины, 2019)
Background: fever of unknown origin is one of the diagnoses more difficult in our area, because it involves monitoring of a complex algorithm of several procedures to establish its cause and con frequently takes too long before any explanation. Therefore, the objective is to get to your diagnosis etiologic and to do a particular series of steps.Objective: to describe the most frequent causes of classical fever of unknown origin in the hospital setting and make a simplified diagnostic search algorithm for this pathology.Methods: a case-series study of 85 patients admitted to the Hospital Obispo Polanco with a diagnosis of fever of unknown origin conducted from 2013 to 2018 in the therapeutic services except for pediatrics and surgery units. The study variables included age, sex, complementary studies (variables from humoral, microbiological and biopsies), results obtained, diagnosis of each patient, treatment.Results: of all patients, 23 (27 %) had infections, of which 14 (16 %) of respiratory focus, 6 (7 %) of urinary focus, 2 (2 %) of abdominal focus and 1 (1 %) of the skin focus. Seven patients (8 %) had neoplasms, three of which (3 %) of respiratory origin, three of digestive tract (3 %) and one of prostatic origin (1 %). In four patients (5 %) were diagnosed of the rheumatic diseases. In 51 (60 %) patients not be could diagnose any cause of fever of unknown origin.Conclusions: the first cause of fever of unknown origin is diseases of unknown etiology with 60 % (51 cases) without being able to identify the clear focus. Among the known etiologies, the most private pathology is infectious bacterial diseases of the respiratory and urinary tracts (27 % — 23 patients). The third place is occupied by oncological diseases with a predominance of malignant pulmonary neoplasms (8 % — 7 patients). Rheumatological diseases occupy the last place and, in this study, accounted for only 5 % (4 patients).